(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The release of ChatGPT technology identified the large language models as a new disruptive technology, which changes the behaviours of society and its attitude towards the presence of artificial intelligence in everyday life. The tourism industry is one of the economic sectors, which will be impacted by the large language models through personalized marketing and advertisements. A common approach to capture the attention of AI-centric tourists, who want to get answers to their questions without manually researching the topic or using services of the travel advisors, is to integrate a chatbot or virtual assistant in the tourism information system. We applied this approach to the promotion of tourism in East Latvia (Latgale) by rapidly developing a chatbot by using a prompt method with context-oriented material. Two models were prepared for tourism promotion in Latgale. The models were evaluated through a pilot survey to understand the satisfaction of target users. The data analysis was applied. The study identified the importance of trustworthy information and answer saturation. The trade-off between dialog freedom and trustworthiness of answers can be achieved through the development of microservices, which are grouped as one system to direct conversation with chatbot. The appropriate conceptual models are presented in the article.